PENGARUH DIGITAL MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN - Putra, I Gusti Ngurah Bagus Suarna; Wardana, Miko Andi; Darsana, I Made (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Strategy implementation digital marketing is the right choice to attract tourists, and help restore Indonesian tourism after the COVID-19 pandemic. Carangsari Tourism Village continues to increase innovation and creativity to attract visitors. While conventional promotions cannot be carried out, Carangsari Tourism Village develops promotions in many ways digital so that the process of conveying information by word of mouth is digital increasingly supported. This study aims to determine the influence digital marketing and electronic word of mouth mediated by interest in visiting on the decision to visit tourists in Carangsari Tourism Village. This study uses a quantitative approach. Data were collected through questionnaires, direct interviews, and literature. The sampling technique used in this study is accidental sampling. Respondents from this study were 176 people who had visited Carangsari Tourism Village. The data analysis technique used is SEM-PLS analysis using the SmartPLS 3.0 program. The results of this study indicate that digital marketing significant effect on the decision to visit, EWOM significant influence on the decision to visit, digital marketing significant effect on interest in visiting, EWOM significant effect on the intention to visit, the intention to visit has a significant effect on the decision to visit, digital marketing which is mediated by interest in visiting has a significant effect on visiting decisions, and EWOM which is mediated by interest in visiting has a significant effect on visiting decisions